The widow and son of Soq'a Machu: The case of a tolerated, accepted and demanded infanticide - Flores Ochoa, Jorge A. (1973)
In the studies of the communities of the Peruvian highlands, there are few works that deal with social control, and even fewer those that relate oral traditions, popular beliefs and superstitions, in short, the different characters of Andean folklore, with the various mechanisms of social control. There are quite a few descriptions of folkloric facts, but I think that few of them have tried to see a relationship between what is popular belief and the way in which they are used to coerce people, in order to force them to follow the lines of behavior valued by the group. Many times even at the expense of other individual values ​​of its members, who suffer greater damage in favor of society, considered as a unit.